2021
DOI: 10.3389/fonc.2021.617621
|View full text |Cite
|
Sign up to set email alerts
|

YBX3 Mediates the Metastasis of Nasopharyngeal Carcinoma via PI3K/AKT Signaling

Abstract: The metastasis of nasopharyngeal carcinoma (NPC) is a complex process associated with oncogenic dysfunction, the deciphering of which remains a challenge and requires more in-depth studies. Y-box protein 3 (YBX3) is a DNA/RNA binding protein associated with gene transcription, DNA repair, and the progression of various diseases. However, whether and how YBX3 affects the metastasis of NPC remains unknown. Thus, in this study, we aimed to investigate the role of YBX3 in the metastasis of NPC and determine its un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 42 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…Intracellular Adhesion Molecule 1 ( Icam1 ), Y-box Binding Protein 3 ( Ybx3 ), Ras-related C3 Botulinum Toxin Substrate 1 ( Rac1 ) and Glycogen Synthase Kinase-3 beta ( Gsk3b ) gene expression was significantly increased following intracranial H-FIRE. YBX3 functions as a DNA/RNA binding protein that regulates transcription, translation and DNA repair; thus, the increase in gene expression observed is not surprising given the impact intracranial H-FIRE has on gene regulation [ 58 ]. ICAM1 is expressed on brain endothelial cells and plays a major role in immune cell trafficking; thus, H-FIRE appears capable of facilitating local immune cell infiltration [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular Adhesion Molecule 1 ( Icam1 ), Y-box Binding Protein 3 ( Ybx3 ), Ras-related C3 Botulinum Toxin Substrate 1 ( Rac1 ) and Glycogen Synthase Kinase-3 beta ( Gsk3b ) gene expression was significantly increased following intracranial H-FIRE. YBX3 functions as a DNA/RNA binding protein that regulates transcription, translation and DNA repair; thus, the increase in gene expression observed is not surprising given the impact intracranial H-FIRE has on gene regulation [ 58 ]. ICAM1 is expressed on brain endothelial cells and plays a major role in immune cell trafficking; thus, H-FIRE appears capable of facilitating local immune cell infiltration [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Focal adhesion kinases (FAKs) are a class of cytoplasmic non-receptor protein tyrosine kinases that belong to the protein tyrosine kinase (PTK) superfamily and are therefore also known as PTK II (32). FAKs can integrate signals from integrins, growth factors and mechanical stimuli to activate intracellular PI3K/Akt, Ras/MAPK and other signaling pathways to regulate cell growth (33)(34)(35). Numerous studies on the association of FAKs with different types of cancers have shown a close link between FAKs and the biological mechanisms that promote cancer development and progression (36).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated serum c-Src levels are associated with a poor prognosis in NPC patients [ 44 ]. The expression of YBX3 is positively correlated with NPC metastasis [ 45 ]. An abnormal expression of COX-2 is associated with recurrence and a poor prognosis in NPC patients [ 46 ].…”
Section: Discussionmentioning
confidence: 99%